2013
DOI: 10.1007/s10899-013-9431-4
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness Facets and Sensation Seeking as Predictors of Problem Gambling Among a Sample of University Student Gamblers

Abstract: Understanding the factors that contribute to problem gambling (PG) is imperative. Individual differences in sensation seeking (SS), as measured by the Sensation Seeking Scale Form (SSS-V), have been found to be predictive of PG among university student samples. However, what is less clear, is if the four SSS-V subscales capture unique facets of SS that are particularly predictive of PG. Much less studied than SS, competitiveness has also been found to be predictive of PG. The Competitiveness Orientation Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…This finding is consistent with the results of a previous study, showing that individuals gambling only in casinos had a less negative risk profile than those who combined casino gambling with other activities (Franco et al 2011). Yet, casino gamblers were closer to extensive gamblers than to rare or non-gamblers with regard to levels of aggression/hostility, sensation seeking and sociability (traits related to gambling problems, see Harris et al 2013;Zuckerman and Kuhlman 2000), but had lower levels of anxiety/neuroticism and avoidant coping and higher levels of problem-focused coping than extensive gamblers. This may indicate that casino gamblers may gamble rather for recreational purposes than extensive gamblers, possibly because they are less prone to anxiety and stress (associated with neuroticism/anxiety) and use more adaptive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with the results of a previous study, showing that individuals gambling only in casinos had a less negative risk profile than those who combined casino gambling with other activities (Franco et al 2011). Yet, casino gamblers were closer to extensive gamblers than to rare or non-gamblers with regard to levels of aggression/hostility, sensation seeking and sociability (traits related to gambling problems, see Harris et al 2013;Zuckerman and Kuhlman 2000), but had lower levels of anxiety/neuroticism and avoidant coping and higher levels of problem-focused coping than extensive gamblers. This may indicate that casino gamblers may gamble rather for recreational purposes than extensive gamblers, possibly because they are less prone to anxiety and stress (associated with neuroticism/anxiety) and use more adaptive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons to that may be that some personality traits related to gambling problems and substance use (Harris et al 2013;Zuckerman and Kuhlman 2000), such as high levels of aggression/hostility and sensation seeking, may predispose private gamblers to negative gambling outcomes and substance use comorbidities. An alternative explanation may be that gambling activities in private settings are subject to no policy regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSS is split into four subscales: thrill and adventure seeking, experience seeking, disinhibition, and boredom susceptibility. Unfortunately, SSS subscales are rarely reported separately (Harris, Newby, & Klein, 2015). In one of the few studies that has distinguished between subscales, Fortune and Goodie (2010) found that the disinhibition and boredom susceptibility factors of sensation seeking, as measured by the SSS, were related to pathological gambling but experience seeking and thrill and adventure seeking were not associated with pathological gambling.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Donati et al (2013) in a study with Italian adolescents found that sensation seeking was a significant predictor of problem gambling. Furthermore, a more recent study conducted by Harris et al (2015) with a sample of college students showed that the total score on sensation seeking was significantly correlated with problem gambling severity. Overall, these findings suggest that youth problem gamblers are more inclined to be socially disinhibited and easily bored with routine, and highlight the need to further examine the mechanisms of this variable in order to better identify personality characteristics that can facilitate the development of gambling-related problems, which may also have a preventive value for such risky behaviour.…”
mentioning
confidence: 96%